Implementasi Budaya Keselamatan Pasien Oleh Perawat Instalasi Rawat Inap Di Rumah Sakit King Khalid Najran Arab Saudi - Ade Sariah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
ABSTRACTPatient safety culture is an important factor in reducing incidents. The implementation of a patient safety culture is carried out to protect patients from mismanagement or injury due to interventions and so that nurses are not afraid to report incidents of errors that occur. This study aims to describe the Implementation of Patient Safety Culture by Inpatient Installation Nurses at King Khalid Najran Hospital, Saudi Arabia. This research is a quantitative descriptive study with a cross sectional approach. The research sample was nurses totaling 106 people using probability sampling sampling technique. Data collection was done by using a questionnaire. The analysis used is univariate analysis. The results showed that the nurse's cultural perception was 11.86 (69.28%) in the unfavorable category, the nurse's justice culture was 11.80 (59.01%) in the poor category, the nurse reporting culture was 14.76 (73.82%). ) with good category, nurse learning culture of 13.15 (65.74%) with poor category and nurse information culture of 11.91 (59.53%) with poor category. Based on the results of the study, it can be said that the application of safety culture by inpatient installation nurses at King Khalid Najran Hospital in Saudi Arabia is still said to be poor in its implementation, so it is necessary to improve the implementation of safety safety. The results of this study are expected to be information for hospitals to further improve patient safety so that they can improve the quality of health services to patients in hospitals.